2007
DOI: 10.1158/1078-0432.ccr-07-0252
|View full text |Cite
|
Sign up to set email alerts
|

Excision Repair Cross Complementation Group 1 Immunohistochemical Expression Predicts Objective Response and Cancer-Specific Survival in Patients Treated by Cisplatin-Based Induction Chemotherapy for Locally Advanced Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: To assess the correlation of excision repair cross complementation group 1 (ERCC1) immunohistochemical expression with objective tumor response and cancer-specific survival in patients with locally advanced head and neck squamous cell carcinoma treated with cisplatinbased induction chemotherapy. Experimental Design: The initial cohort was composed of 107 patients who were treated from 1992 to 1996 by an induction chemotherapy regimen for locally advanced head and neck squamous cell carcinoma. p53 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
3
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 26 publications
8
97
3
1
Order By: Relevance
“…Secondly, wide heterogeneity of detection methods has been reported in studies under consideration [11][12][13][14][15][22][23][24][25][26][27][28][29][30][31][32][33]. It has been shown that ERCC1 immunodetection faces several methodological challenges including tissue processing, rates of interobserver agreement, geographic variation in protein expression and, most importantly, lack of the standardized cutoff value in semi-quantitative IHC [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, wide heterogeneity of detection methods has been reported in studies under consideration [11][12][13][14][15][22][23][24][25][26][27][28][29][30][31][32][33]. It has been shown that ERCC1 immunodetection faces several methodological challenges including tissue processing, rates of interobserver agreement, geographic variation in protein expression and, most importantly, lack of the standardized cutoff value in semi-quantitative IHC [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…ERCC1 expression stratified by human papillomavirus (HPV) status in head and neck cancers. At the end, 17 studies containing 1288 patients were included in metaanalysis [11][12][13][14][15][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The similar mete-analysis was performed by Chen and the same conclusion was gained (Chen et al, 2010). In addition, many papers evaluated the relation between ERCC1 status and response to chemotherapy have been reported in various human cancers including Colorectal Cancer, bladder cancer, cervical cancer, Head and Neck Cancer, and most of studies showed ERCC1 expression was a predictor of response to chemotherapy (Handra-Luca et al, 2007;Braun et al, 2008;Kim et al, 2009;Ishibashi et al, 2010;Kim et al, 2010;Hayes et al, 2011;Kawashima et al, 2011;Park et al, 2011;Sun et al, 2012). In 2008, Lin et al performed a cohort study to evaluate the difference of ERCC1 protein expression levels between 36 sensitive cases and 27 resistant cases of serous ovarian cancer receiving neoadjuvant chemotherapy and demonstrated that ERCC1 protein expression levels in resistance group of serous ovarian cancer were significantly higher than those of sensitivity group, and Lin et al's study was in accordance with our meta-analysis (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 57%